STUDENT’S DIFFICULTIES IN TRANSFORMATION GEOMETRY COURSE VIEWED FROM VISUALIZER VERBALIZER COGNITIVE STYLE - Rohmah Indahwati (Prodi Pendidikan Matematika FKIP Universitas Madura, 2023)
This study aims to determine the difficulties of students in the geometry transformation course in terms of visualizer and verbalizer cognitive style, especially in the concept of mapping a transformation. The research subjects were students of the transformation geometry class at the Mathematics Education Study Program at the University of Madura. This research is a qualitative descriptive study. Based on the results of the study, it was found that the difficulties of students with cognitive visualizer and verbalizer styles tended to be the same, which included (1) difficulty visualizing the definition of a transformation (2) difficulty in proving a transformation (3) difficulty determining the result area of a mapping. The Visualizer subject answers all the questions given and tries to describe the definition of the transformation given, although it is still not precise, it is better than the subject verbalizer. Verbalizer subjects, who are essentially easier to process information in the form of writing, are constrained by the arrangement of mathematical sentences and mathematical symbols which make the subject reluctant to try to answer questions. From the results of the analysis it was also revealed that the causes of the subject's difficulties were influenced by several aspects, namely, lack of mastery of basic geometric concepts, weak of reasoning ability and difficulties in mathematical operationsKeywords: Student Difficulties, Transformation Geometry, Visualizer Verbalizer Cognitive Style